WEB-BASED PROBLEM-BASED LEARNING TO IMPROVE SCIENCE LITERACY AND PROBLEM-SOLVING : A SYSTEMATIC REVIEW - Aulia, Winda; Maryati, Maryati (Universitas Bhinneka PGRI, 2026)
This systematic review explores the implementation of Web-Based Problem-Based Learning (WB-PBL) as an innovative instructional approach to improve students' science literacy and problem-solving skills. In response to Indonesia’s low performance in international assessments such as PISA, this study highlights the urgency for student-centered, technology-integrated, and contextually meaningful learning models. Using a descriptive qualitative method with the PRISMA, 17 peer-reviewed articles published between 2015 and 2025 were analyzed. The review synthesizes research findings regarding learning outcomes, digital platforms, and instructional designs employed in WB-PBL. Results indicate that WB-PBL, especially when implemented through e-modules, Google Sites, FlipHTML5, and interactive worksheets, consistently enhances students’ critical thinking, conceptual understanding, and engagement. The integration of local contexts and web-based interactivity further strengthens learning motivation and scientific reasoning. However, challenges such as limited digital literacy, access inequality, and teacher readiness persist. This review concludes that WB-PBL is not only a pedagogical alternative but also a transformative solution aligned with 21st-century learning goals and the Indonesian Merdeka Curriculum. It offers insights for educators, researchers, and policymakers to advance science education through effective, scalable, and inclusive practices.